The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.schres.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating dermatoglyphic asymmetries in youth at ultrahigh-risk for psychotic disorders

Abstract: Fluctuating dermatoglyphic asymmetry represents one specific class of minor physical anomaly that has been proposed to reflect prenatal insult and vulnerability to psychosis. However, very little is known about fluctuating dermatoglyphic asymmetry in youth showing symptoms of ultrahigh risk (UHR) for psychosis. Using high-resolution photographs of fingerprints and clinical interviews, the UHR group in this study showed greater fluctuating dermatoglyphic asymmetry compared to controls; however, this was not fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The effect size, however, was moderate (Cohen's d = 0.44), by Cohen's [279] criteria. More recently, the same research team [97,98] has shown that a larger sample of adolescents at risk for psychosis also have greater dermatoglyphic asymmetry, with a similar effect size (Cohen's d = 0.48). The authors suggest that the results of both studies support the Diathesis-Stress Model in which prenatal insults disturb the structure and function of the hippocampal region, which regulates the hypothalamic-pituitary-adrenal axis.…”
Section: Psychologymentioning
confidence: 95%
See 2 more Smart Citations
“…The effect size, however, was moderate (Cohen's d = 0.44), by Cohen's [279] criteria. More recently, the same research team [97,98] has shown that a larger sample of adolescents at risk for psychosis also have greater dermatoglyphic asymmetry, with a similar effect size (Cohen's d = 0.48). The authors suggest that the results of both studies support the Diathesis-Stress Model in which prenatal insults disturb the structure and function of the hippocampal region, which regulates the hypothalamic-pituitary-adrenal axis.…”
Section: Psychologymentioning
confidence: 95%
“…Nine years later, Van Valen [4] used an offshoot of the correlation coefficient (r), 1 − r 2 , the coefficient of indetermination, as an estimate of the unshared variance (i.e., the random variation). Most early researchers working with humans, including Bailit et al [2], Micle and Koblyliansky [90], Mellor [38], and others [94-96] followed Holt's [45] and Van Valen's [4] lead (but see [77,82,83,97,98]). Evolutionary biologists, on the other hand, favored some variant of Mather's [3] approach and soon found justification for it.…”
Section: Dermatoglyphic Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect evidence suggests a link between early brain development and increased rates of psychosis from prenatal famine/nutrition (4,5), flu exposure (6,7), and deletions of genes related to early brain development (i.e., 22q11 deletion; 8,9). Furthermore, other established markers of early prenatal development (e.g., dermatoglyphics) relate to psychosis (10,11), but do not provide a direct metric of brain development. Gyrification may provide a more direct metric of early brain development and added insight into abnormal neurodevelopmental processes in psychosis.…”
Section: Backroundmentioning
confidence: 99%
“…ability of an organism to moderate its development against genetic or environmental stresses. Increasing fluctuating asymmetry is in human populations linked to some indicators of developmental stability such as morbidity and number of offspring [43] or length of gestation [26], as well as to specific multifactorial disorders [9,38].…”
Section: Discussionmentioning
confidence: 99%